THE PECULIARITIES OF TRANSLATION OF PHRASAL VERBS INTO UKRAINIAN - I. V. Dvoretska (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2014)
The given paper is devoted to analyzing the peculiarities of phrasal verbs translation into Ukrainian. Phrasal verbs are frequently used not only in everyday English, but also in the official style of communication. Moreover, one should use them in order to communicate fluently and naturally. It is necessary to understand the meanings of phrasal verbs to translate them into the target language properly. The topicality of this study consists in the necessity of solving existing difficulties during translation, as these types of verbs have no direct equivalents in Ukrainian. This research has been carried out on the basis of the text "Pygmalion" written by Bernard Shaw and its Ukrainian translation done by O. Mokrovolsky. Pragmatic and stylistic peculiarities of phrasal verbs translation have been examined in this paper too. To translate a phrasal verb a translator should also take into account the peculiarities of the mentality of the nation as well as background knowledge and context. It is necessary to adapt the text at the target reader to achieve its communicative purpose. Since the absolute equivalents of phrasal verbs translation are virtually impossible, the translator exploits different types of transformations. The translator deals with the lexical and semantic transformations such as concretization, generalization; also he/she can use a lexical equivalent. The ways of translation with the examples have been given in this paper. It is recommended to find the only definition of phrasal verb which would help to differentiate this type of verbs.